"Watch out, here comes feeling!"; Women executives and emotion work. (13th September 2005) - Ross-Smith, Anne; Chesterman, Colleen; Peters, Margaret
In this article, we present findings of an Australia-wide empirical study that investigated the impact of the presence of senior women executives on management cultures. We found that both men and women clearly agreed that the presence of women in senior roles had changed management cultures. When there was a critical mass of women employed at senior levels, both women and men believed that women encouraged greater collaboration, more consultative decision-making processes and more collegial workplaces. Whilst this might represent a welcome shift towards less instrumental management cultures, the findings also strongly resonate with stereotypical images of women's traditional roles in Western culture – roles associated with the domestic sphere. Such perceptions have the potential to disadvantage women executives particularly if women accept that it is their role to manage these aspects of a culture – a scenario which could lead to the reproduction of a gender-based system of relations at the most senior levels in organisations.